The Positive Politeness Strategies Applied in Think Globally Act Locally English Textbook - Ismawati Ike Nugraeni, Andrian Nuriza Johan, (Journal Prakarsa Paedagogia, 2023)
The efficacy of interactions is considerably increased by politeness's contribution. Politeness, which involves paying attention to the appearance of another person, helps social interactions go more smoothly. Politeness, which involves paying attention to the appearance of another person, helps social interactions go more smoothly. Since the purpose of this research was to provide a comprehensive understanding as well as a detailed description of the methods of positive politeness utilized in conversation models found in the textbook, the type of research that was conducted was descriptive-qualitative research. According to the findings of the study, the strategy that is used the most frequently is "Noticing the Hearer Strategy." This is followed by "Exaggerating Strategy" (29.7%), "Including Both Speaker and Hearer Strategy" (24.3%), "Presupposing Strategy" (5.4%), "Intensifying interest to the hearer in the Speaker's Contribution" (2.7%), "Offering Strategy" (2.7%), and "Giving Reason Strategy" (2.7%).